Safer User Interfaces: A Case Study in Improving Number Entry - Harold Thimbleby (IEEE Transactions on Software Engineering, 2015)
Numbers are used in critical applications, including finance, healthcare, aviation, and of course in every aspect of computing. User interfaces for number entry in many devices (calculators, spreadsheets, infusion pumps, mobile phones, etc.) have bugs and design defects that induce unnecessary use errors that compromise their dependability. Focusing on Arabic key interfaces, which use digit keys 0-9-· usually augmented with correction keys, this paper introduces a method for formalising and managing design problems. Since number entry and devices such as calculators have been the subject of extensive user interface research since at least the 1980s, the diverse design defects uncovered imply that user evaluation methodologies are insufficient for critical applications. Likewise, formal methods are not being applied effectively. User interfaces are not trivial and more attention should be paid to their correct design and implementation. The paper includes many recommendations for designing safer number entry user interfaces.